Physical Activity in Fontan Patients Relates to Quality of Life and Sleep Quality - Callegari, Alessia; Faeth, Kathrin; Pfammatter, Charlène; Jung, Ruedi; Berger, Florian; Burkhardt, Barbara; Valsangiacomo Buechel, Emanuela R. (Frontiers in Cardiovascular Medicine, 2022)
Background and Aim: Fontan patients tend to have reduced physical exercise capacity. This study investigates physical activity (PA) and its relationship to exercise capacity, heart rates, cardiac function, biomarkers, health-related quality of life (HRQoL), and sleep quality. Methods: Cardiovascular magnetic resonance (CMR), exercise testing (CPET), 24h-ECG, and blood samples were prospectively performed in 38 patients, age 13 (11-16) years. PA was assessed by accelerometer during 7 consecutive days. HRQoL was self-assessed with KIDSCREEN-27 and SF-36 according to patients’ age; sleep quality with Pediatric Sleep Questionnaire (PSQ) and Pittsburgh Sleep Quality Index (PSQI). Results: Daily moderate to vigorous physical activity (MVPA) was in median (IQR) 40 (28-57) minutes; 7/38 (18%) patients reached the recommended 60minutes/day of MVPA. MVPA did not correlate with gender, age, single ventricle morphology, time from Fontan, heart rate, ventricular volumes, and ejection fraction at CMR, biomarkers, or CPET. Physical well-being (r=0.33, p=0.04), autonomy (r=0.39, p=0.03), and social support (r=0.43, p=0.009) assessed using the KIDSCREEN-27, and both physical (r=0.57, p=0.03) and mental (r=0.54, p=0.04) domains of the SF-36 questionnaire correlated with daily minutes of MVPA. PSQI global sleeping score (r=-0.7, p=0.007), and PSQ scales for behaviour (r=-0.36; p=0.03) correlated with daily minutes of MVPA. Conclusion: Only 18% of the Fontan patients meet the recommendation for daily MVPA. Measures of exercise capacity, cardiac function or chronotropic competence are not correlated to daily physical activity. In contrast, HRQoL and sleep quality seem to be associated with regular physical activity.